Does education predict gender role attitudes?: Evidence from European datasets - Sumit S. Deole; Tugba Zeydanli (Global Labor Organization (GLO), 2021)
This paper presents the first empirical evidence of the causal impact of individuals' education on their attitudes towards traditional gender roles in Europe. We employ two national panel datasets from the UK and Switzerland and a repeated cross-sectional dataset with information from 13 Western European countries for the analysis. To estimate the causal impact of education on gender role attitudes, we exploit the exogenous variation in individuals' education induced by the compulsory school reforms implemented in European countries after World War II. Our results suggest that an additional year of education instigates egalitarian gender role attitudes equivalent of 0.1-0.3 of a standard deviation. While education's moderating effect is particularly prominent among women, we find no evidence of effect heterogeneity concerning individuals' religiosity. Our findings are robust to numerous checks performed and are briefly discussed for their policy relevance.
Keywords: J16; J78; C26; 330; Gender role attitudes; education; compulsory schooling reforms; IV strategy